Stammer Speech Impediment of Jessie Davies in “Talk Twenties” Podcast - As Syadza, Nurrisca Ubahiroh; Indah, Rohmani Nur (English Education Study Program Faculty of Teacher Training and Education, 2024)
Speaking was challenging for those with stammering as language impediment. To just produced sounds, syllables, phrases, or sentences required some effort on their part. Each individual with stammering impediment had challenges including Jessie Davies, a popular youtuber despited her stammering impediment. This research aimed to explored the types of stammering impediment in Jessie Davies's utterances and how she experiences it as an adult stammerer. The descriptive approach used in this study as the research design. The processed of description includes describing, noting, analyzing, and interpreting a phenomenon's nature, makeup, or process. This study found that in Jessie Davies' utterances, the type of stammering that often appeared was identified, namely the repetition type. It was also found that the type of stammering that appeared the least was the broken word type. She also experienced difficulties in the form of failure in communication and difficulty getting friends and partners.